The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.2337/diacare.26.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Target-Seeking Behavior of Plasma Glucose With Exercise in Type 1 Diabetes

Abstract: OBJECTIVE -To investigate the reproducibility of the plasma glucose (PG) response to exercise in subjects with type 1 diabetes on a nonintensive insulin regimen.RESEARCH DESIGN AND METHODS -Subjects cycled for 45 min at 50% VO 2max on two occasions (studies 1 and 2) either 1 h after lunch and usual insulin (protocol A) or after overnight fasting without morning insulin (protocol B). Identical diet, activity, and insulin (twice daily neutral and intermediate) were maintained before and during each study day. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
6
31
0
Order By: Relevance
“…Another unexpected finding is that without prior carbohydrate intake, moderate-intensity exercise with or without repeated sprints did not significantly affect blood glucose levels. These different experimental conditions may explain the absence of an exercise-mediated fall in blood glucose reported here, as others have shown similar findings when exercise is performed after a prolonged fast [15][16][17][18]. Our findings contrast with those of Guelfi et al [9], where moderate-intensity exercise, with and without repeated sprints, was shown to result in a significant fall in blood glucose level, albeit to a lesser extent with the latter.…”
Section: Discussionsupporting
confidence: 54%
“…Another unexpected finding is that without prior carbohydrate intake, moderate-intensity exercise with or without repeated sprints did not significantly affect blood glucose levels. These different experimental conditions may explain the absence of an exercise-mediated fall in blood glucose reported here, as others have shown similar findings when exercise is performed after a prolonged fast [15][16][17][18]. Our findings contrast with those of Guelfi et al [9], where moderate-intensity exercise, with and without repeated sprints, was shown to result in a significant fall in blood glucose level, albeit to a lesser extent with the latter.…”
Section: Discussionsupporting
confidence: 54%
“…These findings extend those of MacDonald et al, 3 who reported in a prospective (though uncontrolled) outpatient case series that 48 of 300 (16%) patients with T1DM (age 4 to 24 years) self-reported at least 1 episode of moderate or severe hypoglycemia occurring 4 or more hours after exercise during a 2-year period. Although a number of studies have evaluated the incidence of hypoglycemia during or immediately after exercise, [13][14][15][16][17] we are not aware of a previous study that has systematically evaluated the occurrence of overnight hypoglycemia after exercise in children or in adults.…”
Section: Discussionmentioning
confidence: 95%
“…One of the most discussed topics with patients around exercise management is the notion that there is unexplainable inter‐patient variability in the glucose responses to exercise . According to a limited number of small studies, a higher pre‐exercise blood glucose concentration tends to be associated with a greater absolute drop in glycemia during prolonged aerobic exercise .…”
Section: Introductionmentioning
confidence: 99%